I alpha-hydroxycholecalciferol: a treatment of renal bone disease. Issue 5948 (4th January 1975) - Catto, G R; MacLeod, M; Pelc, B; Kodicek, E
Abstract : Three patients with chronic renal failure on maintenance haemodialysis have been treated with 1 alpha-hydroxycholecalciferol (1 alpha-OHCC), a synthetic vitamin D analogue. A daily dose of 2 mug by mouth produced a significant increase in both calcium absorption from the gastrointestinal tract and calcium content of bone. Treatment with 1 alpha-OHCC appears to be effective in cases of metabolic bone disease associated with chronic renal failure.